Pelatihan Membaca Syair Siswa Kelas XII SMA Negeri 2 Dumai - Sudirman Shomary; Idawati Idawati; Nurul Aini Sudirman (UIR Press, 2022)
Reading poetry is one of the teaching of literature in the High School Curriculum. As a form of literary work, poetry has many benefits for children's development, namely for High School students. For High School students, reading poetry is sometimes a scary thing or a scourge for them, even though they enjoy learning to read poetry. Most students still think learning to read poetry is a difficult and scary lesson. Every time there is a poetry reading competition, the teacher finds it difficult to find students who are willing and brave in reading poetry. This is because students are not used to reading poetry in front of people. The problem of students in reading Malay poetry is the lack of students' understanding both theoretically and practically in mastering dynamic stress; (b) tone pressure (intonation); (c) tempo pressure. The solution is to conduct poetry reading training for students of SMA Negeri 2 Dumai, Dumai City. The method of community service uses a descriptive method, meaning it is descriptive to describe what it is. This service is in the nature of collecting, managing, and analyzing the data presented as it is in accordance with the problems in the field. The descriptive method was used because the author wanted to accurately assess the ability of the students of SMA Negeri 2 Dumai, Dumai City, in reading poetry. Based on the implementation of